Les hasards de la variole - Jean-Marc Rohrbasser (Astérion)
The necessity of a calculation aiming to evaluate a risk can be revoked in doubt when the question is to make a decision in a situation of uncertainty, all the more when the question is about life or death. In the controversy opened on the opportunity to inoculate the smallpox, D'Alembert’s position constitutes an exemplary case of scepticism concerning the application of the mathematics, and in this particular case the probability theory, to decisions relative to the human life. D’Alembert, indeed, disputes in the social mathematics the power to describe human phenomena by looking for regularities and for formalizations without separating the mathematical and probability dimensions of the philosophic and ethical ones. By following the debate which, in the middle of the 18th century, takes place between the French mathematician and his Swiss counterpart Daniel Bernoulli, we attend one of the episodes of the slow gestation of the notions of risk-taking, decision and rationality.